METHODS USED IN TRANSLATING METAPHOR IN A NOVEL ENTITLED “ILLEGITIMATE TYCOON” BY JANETTE KENNY - Dolli Rotua Sinaga; Carolina Pakpahan; Januar Tumbuan Manurung; Ermina Waruwu (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2020)
This study is primarily aimed to find out the methods used in translating metaphor in a novel entitled “Illegitimate Tycoon” by Janette Kenny and the translation entitled “Dihantui Masa Lalu”. The writer applied descriptive qualitative research design in conducting this study. It is a design which focuses on the natural characteristics of data, in which the writer described and elaborated the findings of the study. The writer applied Newmark’s theory of methods of translation (word-for-word translation, literal translation, faithful translation, semantic translation, adaptation translation, free translation, idiomatic translation, and communicative translation) in analyzing the data. Based on the data analysis, the writer found that from 207 data of metaphor clauses/phrases, the translator used 5 methods from 8 methods of translation. Free translation was used 159 times (76,81%), Literal Translation was used 39 times (18,84%), Semantic Translation was used 6 times (2,91%), Idiomatic Translation was used 2 times (0,96%), and Adaptation was used 1 times (0,48%). It means that mostly the translator used free translation in translating metaphor. The most dominant method used in translating metaphor in a novel “Illegitimate Tycoon” by Janette Kenny is Free Translation. The translator used free translation mostly is because the translator usually paraphrase the original text but the SL manner, content, and form are not used.